Influência da idade, da função renal, dos níveis séricos de cálcio iônico e de dois diferentes imunoensaios na relação entre 25-hidroxivitamina d e paratormônio - Lilian Mello Soares (2015)
It has been noticed an increase in the prevalence of hypovitaminosis D since the introduction of reference values based on functional measurements, such as 25-hydroxyvitamin D (25OHD) levels that maximally suppress parathyroid hormone (PTH) secretion. Although this approach has not led to a definitive threshold, 30 ng/mL has been widely adopted as the cutoff value for defining optimal vitamin D status. The objective of this study was to analyze the relationship between 25OHD and PTH simultaneously measured, in order to assess the appropriateness of single universal thresholds for vitamin D. The influence of age, renal function and ionized calcium levels on this relationship was evaluated, as well as the impact of using two different assays for 25OHD testing (Architect® and LIAISON®). This was a cross-sectional analysis of 23,259 paired serum PTH and 25OHD levels, measured from January to December 2012. There was no evidence of a plateau relationship between these two analytes. For similar 25OHD concentrations, PTH medians were consistently higher with advancing age and in the subpopulation with impaired renal function and/or abnormal ionized calcium levels. Using different immunoassays for 25OHD testing had no significant impact on its relationship with PTH. In conclusion, single universal reference values are not suitable for assessing vitamin D status. Age, renal function and ionized calcium levels of the studied population should be taken into account in the definition of vitamin D optimal concentrations and in the interpretation of 25OHD results.